Peran Manajemen Hubungan Masyarakat dalam Upaya Meningkatkan Kualitas Mutu Pendidikan di Sekolah - Septiani, Iin; Rifqi, Muhammad; Setiyadi, Bradley (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to analyze the strategic role of public relations management (PR) in improving the quality of education in schools through various communication mechanisms and community involvement. PR has an important role as a liaison between schools and the community in building trust, disseminating information, and creating a more transparent and participatory educational environment. This study uses a library research method by reviewing various academic literature, scientific journals, and policy documents relevant to PR management in educational institutions. The results of the study indicate that effective communication strategies, both through digital media, routine meetings, and institutional publications, have a positive impact on the image of the school and increase community involvement in the educational process. In addition, well-managed PR can strengthen the relationship between schools and various stakeholders, including the government, the business world, and social organizations, thus supporting the development of more sustainable education programs. The impact of the implementation of optimal PR management is also seen in increasing student learning motivation, active participation of parents in education policies, and improving the quality of teaching through teacher training programs and the provision of more adequate educational facilities. Thus, the role of PR in education is not just an administrative function, but also a strategic element that contributes to creating a more inclusive, innovative, and quality education ecosystem.